CAPITAL MARKET ACCURACY IN PREDICTING ECONOMIC CONDITIONS (STUDY ON THE INDONESIA STOCK EXCHANGE) - Andry Irwanto; I Made Narsa (Berkala Akuntansi dan Keuangan Indonesia, 2016)
This study examines the accuracy of the Indonesian stock market in predicting Indonesia's economic conditions in the future. Economic conditions are represented by changes in the level of Gross Domestic Product and the rate of inflation for a period of 3 months, 6 months and 12 months. Changes in the world economy are represented by changes in the United States stock index, the S&P 500, and the Japanese stock index, the Nikkei 225. The time of the study covers the years 2005 to 2013. Before further processing, a stationary test was carried out for each variable and it was found that all stationary variables . The results show that the Indonesian stock market cannot be used to predict future Indonesian economic conditions (up to 12 months) but is more influenced by world economic conditions as reflected by changes in the United States stock market. Subsequent research can be directed to find out the causes of the inability of the Indonesian stock market to reflect the future economic situation.